Full-scale testing of low adhesion effects with small amounts of water in the wheel/rail interface. (January 2020) - Buckley-Johnstone, L.E.; Trummer, G.; Voltr, P.; Six, K.; Lewis, R.
Abstract: Low adhesion in the wheel/rail contact can be caused by small amounts of water combining with iron oxides. This happens in light rain or at dew point. In small-scale tests, ultra-low adhesion (≤0.05) has not been maintained. The aim here was to see if the mechanism could be realized at a larger scale. Sustained ultra-low adhesion was achieved when water was applied constantly to the wheel/rail contact at a rate of 25μL/s. In these conditions wear debris and oxide was clearly visible in the contact band. Creep force data has been generated that can now be used to inform wheel/rail contact models and multi-body dynamics simulations of train behaviour with a view to developing mitigation. Highlights: Ultra-low friction has been achieved and maintained in a full-scale wheel/rail interface. Threshold amounts of water for low adhesion have been identified. Creep force data generated can be used in train simulations to understand performance in low friction conditions.